2007
DOI: 10.1002/aqc.808
|View full text |Cite
|
Sign up to set email alerts
|

Crunoecia irrorata (Curtis) (Trichoptera: Lepidostomatidae) and conservation of boreal springs: indications of clustering of red‐listed species

Abstract: ABSTRACT1. Crunoecia irrorata is widely dispersed across Europe, but rare and red-listed in Finland. Its geographical range comprises most of the southern boreal zone in Fennoscandia. The species is confined to springs in the north, but occurs also in lower reaches of headwater streams in central and western Europe. It becomes more rare and less abundant towards the limits of its range across Europe, showing diffusive rarity. Glacial history and climate limit the distribution of the species in the north.2. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Our results slightly support the observation that C. irrorata prefers higher pH values (Ilmonen, 2008) and lower values of water hardness (Schindler, 2004). However, based on currently available results, the relatively weak differences, although statistically significant, of these and several other components (e.g., EC, Si, Mg, Na, and K) between springs with and without C. irrorata in our study area do not permit these components to be used as predictive factors for the occurrence of this species.…”
Section: Environmental Preferences and Potential Of C Irrorata As Ansupporting
confidence: 82%
See 3 more Smart Citations
“…Our results slightly support the observation that C. irrorata prefers higher pH values (Ilmonen, 2008) and lower values of water hardness (Schindler, 2004). However, based on currently available results, the relatively weak differences, although statistically significant, of these and several other components (e.g., EC, Si, Mg, Na, and K) between springs with and without C. irrorata in our study area do not permit these components to be used as predictive factors for the occurrence of this species.…”
Section: Environmental Preferences and Potential Of C Irrorata As Ansupporting
confidence: 82%
“…It has been shown that C. irrorata is strongly associated with natural and near-natural springs (Schindler, 2004;Martin and Brunke, 2012), thus serving as an indicator of nearly undisturbed habitat conditions. Additionally, a higher species richness, as well as a higher number of red-listed species, have been reported from springs occupied by C. irrorata compared with springs without this species (Buczyńska, 2008;Ilmonen, 2008). This information also suggests the great potential of this species in terms of the conservation of the co-occurring rare crenic specialists.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…On the other hand, the specific environmental conditions of springs favour the occurrence of several specialized and regionally restricted species (Di Sabatino et al. , 2003; Ilmonen, 2008).…”
Section: Introductionmentioning
confidence: 99%